2019
DOI: 10.1038/s41598-019-48622-2
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge attitude and practice (KAP) of mothers of asthmatic children toward asthma in Khartoum asthma clinics

Abstract: Prevention of asthma attacks is one of the major challenges of public health. Sufficient knowledge and positive attitudes and correct practices are crucial for the prevention of exacerbations. However, there is insufficiency of information in regard to these in Sudan. The aim of this study was to assess the knowledge and to identify the attitude and practice of mothers of asthmatic children concerning their use of inhalers, compliance to preventers and to measure its effect on the severity of the disease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Higher education levels were associated with membership in the “good knowledge” class, consistently with several previous studies [ 2 , 7 , 8 , 14 ]. Indeed, mothers with higher education may be more likely to have prior knowledge and more inclined to gather and absorb new information [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Higher education levels were associated with membership in the “good knowledge” class, consistently with several previous studies [ 2 , 7 , 8 , 14 ]. Indeed, mothers with higher education may be more likely to have prior knowledge and more inclined to gather and absorb new information [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…Current evidence shows that the parental level of asthma-related knowledge may influence asthma management practices [ 2 ] and affect children’s disease control [ 3 , 4 , 5 , 6 ]. Much of the existing literature studying the impact of parental knowledge on childhood asthma outcomes focuses on mothers as the primary caregivers [ 5 , 7 , 8 , 9 , 10 , 11 ], suggesting that asthma in children is majorly managed by mothers. Therefore, assessing mothers’ knowledge and practices is essential for improving the management of childhood asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that better knowledge of asthma self-management is associated with improved lung function, reduction of school absenteeism and ED visits. 9–12 Education of caregivers of children with asthma and clinician-generated AAPs are important components of asthma education and acceptable asthma control as recommended in the practice guidelines. 22 Evidence indicates that written AAPs are effective in the self-management of childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that asthma exacerbations are preventable when patients and caregivers receive formal education for asthma self-management. 3 , 9 Empowering children and caregivers with the required knowledge and self-management skills is necessary to achieve proper asthma control. 10 Despite this evidence, parents of children with asthma continue to have various misconceptions regarding asthma management.…”
Section: Introductionmentioning
confidence: 99%
“…The least knowledge was about bluish discoloration of lips and nails or peripheral cyanosis (45.5%). In Khartoum, 85% of mothers explored cough and dyspnoea as the main symptoms of asthma (19) , while dyspnoea, wheezing, chest tightness, and persistent cough were the main symptoms exhibited by elementary school teachers (20) .…”
Section: Discussionmentioning
confidence: 99%